Audio and Video Courses for Teaching L2 / FL Italian: Interactional, Linguistic and Pedagogical Aspects - Ferroni, Roberta; Pauletto, Franco (Revista de Italianística, 2022)
This study aims to explore the interactional, linguistic, and pedagogical characteristics of the video courses that accompany five L2/FL Italian textbooks. The qualitative analysis confirms that these teaching aids share many aspects with the genre of the television sitcom, both in terms of the varieties of spoken language and of some interactional patterns. The fine analysis of an episode has in fact highlighted some problematic aspects concerning the temporality and sequentiality of the actions, which make these interactions unnatural. The language spoken in these sitcoms (which we define as pasteurized) is a neostandard Italian characterized by little diatopic variation. Furthermore, from a pedagogical standpoint, analytical activities that go beyond comprehension exercises and vocabulary drills are scarce or nonexistent. It is desirable that future teaching materials will reflect the heterogeneity and variability of spoken Italian.